2016
DOI: 10.1016/j.surfcoat.2015.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Deposition, heat treatment and characterization of two layer bioactive coatings on cylindrical PEEK

Abstract: Polyether ether ketone (PEEK) rods were coated via ion beam asssited deposition (IBAD) at room temperature. The coating consists of a two-layer design of yttria-stabilized zirconia (YSZ) as a heat-protection layer, and hydroxyapatite (HA) as a top layer to increase bioactivity. A rotating substrate holder was designed to deposit an even coating on the cylindrical surface of PEEK rods; the uniformity is verified by cross-sectional measurements using scanning electron microscopy (SEM). Deposition is followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…YSZ is used as a thermal barrier coating in high temperature applications and its columnar grain structure helps mediate residual film stresses caused by heat treatment. Recent studies have shown these coatings to exhibit high adhesion strength to PEEK substrates, indicating potential for a robust method for implant surface preparation [24]. In addition, an in vitro study using MC3T3 cells showed promising bone growth on coated samples that underwent post-deposition heat treatments [21].…”
Section: Introductionmentioning
confidence: 99%
“…YSZ is used as a thermal barrier coating in high temperature applications and its columnar grain structure helps mediate residual film stresses caused by heat treatment. Recent studies have shown these coatings to exhibit high adhesion strength to PEEK substrates, indicating potential for a robust method for implant surface preparation [24]. In addition, an in vitro study using MC3T3 cells showed promising bone growth on coated samples that underwent post-deposition heat treatments [21].…”
Section: Introductionmentioning
confidence: 99%
“…PEEK materials also exhibit radiolucent characteristics, implants manufactured from PEEK are compatible with imaging diagnoses, unlike metal implants 3 . Its heat resistance and chemical compatibility with various sterilization techniques, coupled with low cost molding techniques, led PEEK to be a practical and economical material for the manufacturing of medical devices 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Este polímero também possui características radiolúcidas, ou seja, os implantes fabricados a partir do PEEK são compatíveis com diagnósticos de imagem, ao contrário dos implantes metálicos. A sua resistência ao calor e compatibilidade química com várias técnicas de esterilização, juntamente com técnicas de moldagem de baixo custo fazem do PEEK um material prático e econômico para a fabricação de dispositivos médicos [3,4,5,6,7,8,9]. O PEEK trata-se de uma resina termoplástica, semicristalina de cadeia linear aromática interconectadas por grupos cetona (C=O) e éter (-O-).…”
Section: Introductionunclassified
“…Sem a osseointegração (interação do implante com o osso), os implantes podem afrouxar ou migrar, causando dor, deformidade ou deficiência ao paciente. A energia de superfície relativamente baixa do PEEK também pode limitar a osseointegração, e potencializar a encapsulação fibrosa, diminuindo a cicatrização de feridas nas aplicações que exigem a integração [2,8,14,15]. Algumas estratégias têm sido utilizadas para superar o carácter inerte do PEEK.…”
Section: Introductionunclassified